Coordinating Sectoral Policymaking: Searching for Countervailing Mechanisms in the EU Legislative Process - Bernard Steunenberg (Center for Economic Studies and ifo Institute (CESifo), 2003)
In contrast to parliamentary systems, the Council of Ministers, the main legislative body of the European Union, consists of different formations in which national ministers with similar sectoral portfolios participate. This decision-making structure has led to a loss of coherence'. In this paper I analyze several ways to strengthen policy coordination in the Union, including current coordination by the General Affairs Council and further involvement of the European Council. The analysis shows that ex ante-coordination, which is possible when drafting a proposal (for instance, in the case of Coreper) is more effective than ex post-coordination. In addition, imposing a hierarchical structure in which the European Council may review policy initiatives is also rather effective. However, this arrangement raises the question whether such a structure is suitable for a democratic system in which Parliament is not the principal decision-making body.
Keywords: 330